Estratégias e trajetórias políticas de mobilização da juventude: um estudo sobre participação no Conselho Municipal de Juventude de João Pessoa/PB - Oliveira, Geziane do Nascimento (2017)
This dissertation presents reflections and analyzes about youth participation in the Municipal Youth Council of the City of João Pessoa / PB. The Youth Council is configured as a strategic space for youth participation and social control over the public policies focused on this segment. I intend here to focus on the participation of youth in the Council an obstacle that relates to the local socio-political context and the institutional design that structures this space and aims at a social and political order, and youth participation is an important instrument of political action to to provide in this space the guarantee of an effective implementation of the public policies to this segment in the municipality. The objective of this study was to broaden the idea that the participation of these youth disregards the Youth Council is configured in other participatory instances. And that the youth that is not included in the Council uses other channels and participatory mechanisms in the fight for a political action of / towards / with the youths. The methodology learned was based on theoretical reflections, interviews, observations and analyzes of official documents. What we manage to infer was that the Municipal Youth Council requires a political and social order, given the resources derived from this institutionality, however, the youth of which it is part legitimates a participatory discourse, but that is not done in terms of political action. And the youths who draw their trajectory in social movements, besides not realizing the action of the Council, overcome all barriers of political action developing strategies protagonists of struggles and demands for the guarantee of direct of the diverse youths in other spaces, mainly, religious. These young actors lead and coordinate new actions and new forms of youth mobilizations.